Particle-conserving dynamics on the single-particle level - Schindler, Thomas; Wittmann, R.; Brader, J. M. (Physical Review E, 2019)
We generalize the particle-conserving dynamics method of de las Heras et al. [J. Phys.: Condens. Matter 28, 244024 (2016)JCOMEL0953-898410.1088/0953-8984/28/24/244024] to binary mixtures and apply this to hard rods in one dimension. Considering the case of one species consisting of only one particle enables us to address the tagged-particle dynamics. The time-evolution of the species-labeled density profiles is compared to exact Brownian dynamics and (grand-canonical) dynamical density functional theory. The particle-conserving dynamics yields improved results over the dynamical density functional theory and well reproduces the simulation data at short and intermediate times. However, the neglect of a strict particle order (due to the fundamental statistical assumption of ergodicity) leads to errors at long times for our one-dimensional setup. The isolated study of that error makes clear the fundamental limitations of (adiabatic) density-based theoretical approaches when applied to systems of any dimension for which particle caging is a dominant physical mechanism.
CRIS-Team Scopus Importer:2021-04-20